Analisis Manajemen Rantai Pasok Menggunakan Metode Supply Chain Operation Refference - Muhammad Albi Hidayatulloh; Tasya Aspiranti; Umari Abdurrahim Abi Anwar (Bandung Conference Series: Business and Management, 2026)
Abstract. Manufacturing companies play an important role in meeting market demand, yet they often face intense competition and fluctuating demand. In the plastic manufacturing industry, particularly for cotton buds stick products, common challenges include unstable prices and inconsistent quality of polypropylene raw materials, which affect the company’s ability to fulfill customer demand optimally. Therefore, effective supply chain management is required to ensure efficiency across input, process, and output activities. This study aims to analyze the supply chain performance of CV Hammam, Bandung, using the Supply Chain Operations Reference (SCOR) method. This research applies a descriptive quantitative approach with a case study method through interviews, observation, and documentation conducted directly at CV Hammam. The results show that the supply chain performance achieved a Perfect Order Fulfillment (POF) value of 98%, an Order Fulfillment Cycle Time (OFCT) of 8 days, a Cost of Goods Sold (COGS) of 74%, and a Cash to Cash Cycle Time (CTCCT) of 35 days, indicating that the overall supply chain performance is good but still requires improvement, particularly in cost efficiency and cash flow management. Keywords:Supply Chain Management, SCOR, Perfect Order Fulfillment, Order Fulfillment Cycle Time, Cost of Goods Sold, Cash to Cash Cycle Time. Abstrak. Perusahaan manufaktur berperan penting dalam memenuhi kebutuhan pasar, namun sering menghadapi persaingan yang ketat serta permintaan yang bersifat fluktuatif. Dalam industri plastik, khususnya produk batang Cotton Buds, tantangan yang dihadapi meliputi ketidakstabilan harga dan kualitas bahan baku Polypropylene serta keterbatasan perusahaan dalam memenuhi permintaan pada periode tertentu. Oleh karena itu, diperlukan manajemen rantai pasok yang efektif agar proses input, process, dan output dapat berjalan secara efisien. Keberhasilan perusahaan ditentukan oleh kemampuan menghasilkan produk berkualitas, biaya produksi yang efisien, serta ketepatan waktu pengiriman kepada konsumen. Penelitian ini bertujuan untuk menganalisis kinerja manajemen rantai pasok pada CV Hammam Kota Bandung dengan menggunakan metode Supply Chain Operations Reference (SCOR). Jenis penelitian yang digunakan adalah deskriptif kuantitatif dengan metode studi kasus melalui wawancara, observasi, dan dokumentasi langsung di CV Hammam. Hasil pengukuran kinerja rantai pasok menunjukkan nilai Perfect Order Fulfillment (POF) sebesar 98%, Order Fulfillment Cycle Time (OFCT) selama 8 hari, Cost of Goods Sold (COGS) sebesar 74%, dan Cash to Cash Cycle Time (CTCCT) selama 35 hari. Kata Kunci: Manajemen Rantai Pasok, SCOR, Perfect Order Fulfillment, Order Fulfillment Cycle Time, Cost of Goods Sold, Cash to Cash Cycle Time.